Aquinas and Problems of his Time - Verbeke, G. (Mediaevalia Lovaniensia - Series 1/Studia, 1976)
The title of this book calls to mind the colloquium, organised from May 16 to May 19, 1974, in Louvain, by the Institute of Medieval Studies, in collaboration with the Higher Institute of Philosophy and the Faculty of Theology, on the occasion of the 700th anniversary of the death of St Thomas. The book tries to approach the historical context of Aquinas's thought; it endeavours to understand the thinking of St Thomas against his socio-cultural background and to bring to light his attitudes and his reactions to the problems of his time.